Analysis of Green Marketing, Environmental Concern, and Pro-Environmental Behavior on Repurchase Decisions of Compressed Natural Gas (CNG) Fuel Consumers (Case Study of CNG Consumers of Rubber Companies and Oil Palm Companies in South Sumatra) - Bob Olopan Samosir; Ahmad Maulana; Muchin Saggaf Shihab; Aslamia Rosa; Kemas Muhammad Husni Thamrin; M Bagus Barezki (Indonesian Interdisciplinary Journal of Sharia Economics (IIJSE), 2024)
This study examines the influence of green marketing, environmental concern, and pro-environmental behavior on repeat purchase decisions. The scope of this study is rubber companies and palm oil companies with stakeholder respondents. The population and sample in this study are stakeholders in the company. The type of data used in this study is quantitative data. The data source used in this study is Primary Data. The results of the study state that green marketing, environmental concern, and pro-environmental behavior have a positive and significant effect on repeat purchase decisions.